جريمة التزوير في بطاقات الائتمان - نقطي, عبد العزيز (University of Eloued جامعة الوادي, 2022)
تعد جريمة تزوير بطاقات الائتمان من أخطر الجرائم التي يتعرض لها النظام المصرفي بصفة عامة والمتعاملين ببطاقات الائتمان بصفة خاصة كونها تزعزع ثقة التعامل بها، هاته التقنية والتي تبنتها مختلف الدول في مجال الخدمات المصرفية لما توفره من سرعة وأمان في التعامل، أصبحت اليوم عرضة للإعتداء الذي يقوم به محترفو الإجرام عن طريق قيامهم بأعمال غير مشروعة مستغلين في ذلك ما توفره تكنولوجيا المعلومات من تطور في سبيل الإيقاع بضحاياهم، فنجدهم يقومون بتزوير بطاقات الائتمان واستعمالها في السطو على أموال الغير دون وجهة حق، مما يتسبب في إلحاق الضرر بعدة جهات بداية من حامل البطاقة ومصدرها إلى التجار الذين يتعاملون بنظام البطاقات. لذلك قامت معظم الدول بتشديد الرقابة على نظام بطاقات الائتمان وسارعت في ضبط أنظمتها التشريعية والأمنية بما يتماشى والتطور الحاصل في مجال المعلوماتية بغية محاصرة هاته الجريمة والتقليل من انتشارها وملاحقة الجناة وتقديمهم للعدالة. ومهما جرى تعديل هذه التشريعات وضبطها فإنها تبقى عاجزة أمام دهاء وحنكة معتادي الإجرام الذين يقومون في كل مرة بتطوير مهاراتهم عن طريق استغلالهم للتطور التكنولوجي الكبير واستخدمه في التعدي على بطاقات الائتمان. ونتيجة للمخاطر التي تهدد الكيان الوجودي لبطاقات الائتمان عمدت الجزائر كغيرها من الدول إلى إستحداث نصوص قانونية جديدة تتلائم وطبيعة التطور التقني والتكنولوجي في مجال المعلوماتية للحد من جرائم تزوير بطاقات الائتمان وفرض عقوبات على مرتكبيها. Abstract: The crime of forging credit cards, is considered one of the most serious crimes to which the banking system in general and those dealing with credit cards in particular, as it strengthens the confidence of dealing with them. This technology is adopted by different countries in the field of banking services, given the speed and safety it provides in dealing with them. Today it is a crime committed by criminal professionals through illegal activities, taking advantage of the advances made by information technology in order to make their victims. Therefore, we find that most countries have tightened the control of the credit card system, and have been quick to regulate their legislative and security systems in a way that is consistent with the advances in information technology, in order to identify and minimize these crimes, and to prosecute the perpetrators and bring them to justice. However, these laws, regardless of how amended and controlled they are, are sometimes unable to face the usual savvy and malicious of the usual criminals so that each time they develop their skills by exploiting the continuous technological development and using it in credit card infringement. As a result of the risks that threaten the existential entity of credit cards, Algeria, like other countries, has developed new legal texts appropriate to the nature of technical and technological development in the field of informatics to reduce the crimes of credit card fraud and impose sanctions on its perpetrators. Key words: crime, forging, credit, cards, financial, justice, legislative.
The credit cards forging crime
مقال
Keywords: الجريمة ; التزوير ; الائتمان ; بطاقة ; أموال ; العدالة ; التشريعية; The crime of forging credit cards is considered one of the most serious crimes to the banking system in general and those dealing with credit cards in particular, as it weakens the confidence of dealing with them. This technology is